2020
DOI: 10.24042/kons.v7i2.7413
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Multiple Intelligence on Career Planning of Students in Public Vocational High School 3 Klaten

Abstract: The purpose of this study was to determine the role of multiple intelligence on the career planning of students of SMK N 3 Klaten. This research uses qualitative research, with the type of field research (Field Research). The sampling technique used purposive sampling technique. The research subjects were students and teachers of guidance and counseling at SMK N 3 Klaten. Data collection techniques in this study using interviews, observation and documentation. The data validity test used data triangulation whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 1 publication
0
7
0
1
Order By: Relevance
“…SIMPOSIDU is an application system that contains specific student profiles, information on potential talents and interests, information on counseling analysis, information on personal development, information on social learning, and information on careers that are recorded by teachers and students while enrolled at the school in question. It aims to provide the best possible service [11]. There are various items in SIMPOSIDU, including: 1) Personal, social, academic, and career data 2) Student and parent education data 3) Statistics on student counseling data on student performance 5) Data on student self-development 6) Student families' financial information 7) Keeping a study diary Chat functionality.Early on in the activity process.…”
Section: Methodsmentioning
confidence: 99%
“…SIMPOSIDU is an application system that contains specific student profiles, information on potential talents and interests, information on counseling analysis, information on personal development, information on social learning, and information on careers that are recorded by teachers and students while enrolled at the school in question. It aims to provide the best possible service [11]. There are various items in SIMPOSIDU, including: 1) Personal, social, academic, and career data 2) Student and parent education data 3) Statistics on student counseling data on student performance 5) Data on student self-development 6) Student families' financial information 7) Keeping a study diary Chat functionality.Early on in the activity process.…”
Section: Methodsmentioning
confidence: 99%
“…It is demonstrated that a high career maturity equates to a strong planning ability [ 44 ]. Scholars from different countries have studied career planning abilities in different student groups, such as nursing students [ 45 , 46 ], vocational high school students [ 47 ], community college students [ 48 , 49 ], first-year students, and university students [ 1 , 50 , 51 ].…”
Section: Theories and Hypotheses Developmentmentioning
confidence: 99%
“…Hal ini dikarenakan banyak mahasiswa yang memiliki karir berbeda dengan jurusan kuliahnya. Penyebab utamanya adalah karena kurangnya informasi yang mereka dapatkan mengenai kesesuaian antara karir dengan jurusan yang dipilih [Hadi, Aryani, & Suwidagdho, 2020.]. Dampaknya, mereka harus belajar dari awal lagi ketika mulai bekerja.…”
Section: Solusi Dan Targetunclassified